"No Good Deed Goes Unpunished": Ignaz Semmelweis and the Story of Puerperal Fever. (16th May 2016) - Manor, Joshua; Blum, Nava; Lurie, Yoav
Abstract : Ignác Fülöp Semmelweis was born almost 200 years ago, in 1818, to a well-to-do middle class Hungarian family. He started law school in 1837, switched to medicine a year later, and graduated in 1844.